Altered Lipidome Composition Is Related to Markers of Monocyte and Immune Activation in Antiretroviral Therapy Treated Human Immunodeficiency Virus (HIV) Infection and in Uninfected Persons - Bowman, Emily R.; Kulkarni, Manjusha; Gabriel, Janelle; Cichon, Morgan J.; Riedl, Kenneth; Belury, Martha A.; Lake, Jordan E.; Richardson, Brian; Cameron, Cheryl; Cameron, Mark; Koletar, Susan L.; Lederman, Michael M.; et al. (Frontiers in Immunology, 2019)
Background: HIV infection and antiretroviral therapy (ART) have both been linked to dyslipidemia and increased cardiovascular disease (CVD) risk. Alterations in the composition of saturated (SaFA), monounsaturated (MUFA), and polyunsaturated (PUFA) fatty acids are related to inflammation and CVD progression in HIV-uninfected (HIV–) populations. The relationships among the lipidome and markers of monocyte and immune activation in HIV-infected (HIV+) individuals are not well understood. Methods: Concentrations of serum lipids and their fatty acid composition were measured by direct infusion-tandem mass spectrometry in samples from 20 ART-treated HIV+ individuals and 20 HIV– individuals. Results: HIV+ individuals had increased levels of free fatty acids (FFAs) with enrichment of SaFAs, including palmitic acid (16:0) and stearic acid (18:0), and these levels were directly associated with markers of monocyte (CD40, HLA-DR, TLR4, CD36) and serum inflammation (LBP, CRP). PUFA levels were reduced significantly in HIV+ individuals, and many individual PUFA species levels were inversely related to markers of monocyte activation, such as tissue factor, TLR4, CD69, and SR-A. Also in HIV+ individuals, the composition of lysophosphatidylcholine (LPC) was enriched for SaFAs; LPC species containing SaFAs were directly associated with IL-6 levels and monocyte activation. We similarly observed direct relationships between levels of SaFAs and inflammation in HIV uninfected individuals. Further, SaFA exposure altered monocyte subset phenotypes and inflammatory cytokine production in vitro. Conclusions: The lipidome is altered in ART-treated HIV infection, and may contribute to inflammation and CVD progression. Detailed lipidomic analyses may better assess CVD risk in both HIV+ and HIV– individuals than does traditional lipid profiling.